The expression of pre- and postcopulatory sexually selected traits reflects levels of dietary stress in guppies. - Md Moshiur Rahman (Public Library of Science (PLoS), 2014)
Environmental and ecological conditions can shape the evolution of life history traits in many animals. Among such factors, food or nutrition availability can play an important evolutionary role in moderating an animal's life history traits, particularly sexually selected traits. Here, we test whether diet quantity and/or composition in the form of omega-3 long chain polyunsaturated fatty acids (here termed 'n3LC') influence the expression of pre- and postcopulatory traits in the guppy (Poecilia reticulata), a livebearing poeciliid fish. We assigned males haphazardly to one of two experimental diets supplemented with n3LC, and each of these diet treatments was further divided into two diet 'quantity' treatments. Our experimental design therefore explored the main and interacting effects of two factors (n3LC content and diet quantity) on the expression of precopulatory (sexual behaviour and sexual ornamentation, including the size, number and spectral properties of colour spots) and postcopulatory (the velocity, viability, number and length of sperm) sexually selected traits. Our study revealed that diet quantity had significant effects on most of the pre- and postcopulatory traits, while n3LC manipulation had a significant effect on sperm traits and in particular on sperm viability. Our analyses also revealed interacting effects of diet quantity and n3LC levels on courtship displays, and the area of orange and iridescent colour spots in the males' colour patterns. We also confirmed that our dietary manipulations of n3LC resulted in the differential uptake of n3LC in body and testes tissues in the different n3LC groups. This study reveals the effects of diet quantity and n3LC on behavioural, ornamental and ejaculate traits in P. reticulata and underscores the likely role that diet plays in maintaining the high variability in these condition-dependent sexual traits.